Local and Systemic Expression Pattern of MMP-2 and MMP-9 in Complex Regional Pain Syndrome - Escolano-Lozano, Fabiola; Gries, Eva; Schlereth, Tanja; Dimova, Violeta; Baka, Panoraia; Vlckova, Eva; König, Simone; Birklein, Frank (The journal of pain, 2021)
Matrix metalloproteinases (MMP)-2 and MMP-9 play important roles in inflammation as well as in pain processes. For this reason, we compared the concentrations of these enzymes in skin and serum of patients with complex regional pain syndrome (CRPS), other pain diseases and healthy subjects. We analyzed ipsi- and contralateral skin biopsies of 18 CRPS patients, as well as in 10 pain controls and 9 healthy subjects. Serum samples were analyzed from 20 CRPS, 17 pain controls and 17 healthy subjects. All samples were analyzed with ELISA. Concentrations were then compared to clinical data as well as to quantitative sensory testing data.MMP-2 was increased in both ipsi- and contralateral skin biopsies of CRPS patients compared to healthy subjects. While low ipsilateral MMP-2 was associated with trophic changes, contralateral MMP-2 inversely correlated with the CRPS severity. MMP-9 was also locally increased in ipsilateral CRPS skin, and higher ipsi- and contralateral MMP-9 levels correlated with CRPS severity. We conclude that MMP-2 and MMP-9 are differently expressed depending on the clinical phenotype in CRPS. PERSPECTIVE: This article describes an upregulation of MMPs in CRPS and pain controls and shows different expression of MMP-2 and -9 depending on clinical phenotype in CRPS. These results provide evidence that MMP-2 and -9 play a key role in CRPS pathophysiology.
Keywords: Complex Regional Pain Syndromes; Male; Inflammation; Adult; biopsie; komplexní regionální syndromy bolesti; dospělí; mužské pohlaví; Matrix Metalloproteinase 2; kůže; pain; Severity of Illness Index; Complex regional pain syndrome; zánět; lidé; matrixová metaloproteinasa 2; ženské pohlaví; Skin; Complex regional pain syndrome severity score; Humans; matrixová metaloproteinasa 9; inflammation; Biopsy; stupeň závažnosti nemoci; Female; lidé středního věku; matrix metalloproteinases; Matrix Metalloproteinase 9; Middle Aged